39‐2: Highly Sensitive a‐Si:H PIN Photodiode Gated LTPS TFT for Optical In‐Display Fingerprint Identification. Issue 1 (30th May 2018) - Zhou, Xianda; Zhang, Meng; Xu, Yitong; Zhou, Wei; Wang, Kai; Nathan, Arokia; Wong, Man; Kwok, Hoi Sing; Ou, Hai; Chen, Jun; Deng, Shaozhi; Xu, Ningsheng
Abstract : A hybrid optical sensor that is merged with the display driving, low‐temperature polysilicon thin‐film transistor (TFT) is reported. The sensor achieves a fill factor >70% and a photoconductive gain > 10 3 %, which provides a promising solution for in‐display fingerprint identification.